2014
DOI: 10.1039/c4ay00619d
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer solid phase extraction of fungicides from wine samples

Abstract: In order to preconcentrate iprodione fungicide in white wine samples, molecularly imprinted solid phase extraction (MISPE) was developed and optimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It was demonstrated that MISPE is more selective than the classical SPE methodology [5][6][7]. MISPE has proved its efficiency to preconcentrate several analytes in complex matrices such as wine: fungicides [8], Ochratoxin A [9], polyphenolic compounds [10] and histamine [11].…”
Section: Introductionmentioning
confidence: 98%
“…It was demonstrated that MISPE is more selective than the classical SPE methodology [5][6][7]. MISPE has proved its efficiency to preconcentrate several analytes in complex matrices such as wine: fungicides [8], Ochratoxin A [9], polyphenolic compounds [10] and histamine [11].…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study , we synthesized two MIPs specific for iprodione using two polymerization approaches: precipitation (MIPp) and bulk polymerization (MIPb). We compared these two methods of polymerization by molecularly imprinted solid‐phase extraction (MISPE) of iprodione in wine.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of the template during polymerization after bulk imprinting will produce diffusion pathways for the reversible inclusion of small molecules, whereas the large dimensions of microorganisms, ranging up to few micrometers, would hinder their diffusion into the cavities produced by bulk imprinting. MIPs have been applied successfully as biomimetic receptors in various fields such as solid phase extraction [ 22 ], development of sensors for various targets based on different transduction principles [ 23 30 ], drug delivery vehicles [ 31 , 32 ], induced crystallization [ 33 ] and in other different bioapplications [ 34 ]. The most prominent feature of these MIPs is their robustness which helps in creating sensor devices with regeneration and reusability properties.…”
Section: Introductionmentioning
confidence: 99%